Improving the Quality of Beef Burger by Adding Thyme and Rosemary Powder - Manal Abd Al-wahed Al-Sirrag (Journal of Global Pharma Technology, 2018)
The presented study aimed to investigate the effect of the addition of different concentration of rosemary and Thyme powder on the quality and stability of beef burger. Ten treatment  with different concentration of rosemary and thyme T1 (Control) T2(2%) rosemary, T3(4%) rosemary, T4(6%) rosemary, T5(2%)thyme, T6(4%)thyme, T7(6%), T8(rosemary6% + 2% theme), T9( 4% rosemary+ 2%thyme), T10(2%rosemary+4%thyme) were added to beef meat and stored for 0,7,10 weeks. shaped after each period of storage, cooked and evaluated .The obtained results indicated that the best sensory quality was noticed at the lowest concentration 2% of both rosemary and thyme and  there was a significant improvement of odor, flavours, color, and over all acceptability of investigated samples were observed at 0,7,10 weeks. On the other hand, improvement in sensory characteristics could be noticed in sensory characteristics in samples treated with thyme or rosemary 4% concentration after seventh weak storage compared with control samples. High concentration (6%) of added rosemary or thyme to treated samples revealed UN overall acceptability in sensory characteristics.Keywords: Thyme, Rosemary, Herbes, Beef burger Patties and sensory characteristics.